The non-steroidal mineralocorticoid receptor antagonist finerenone improves left ventricular function in preclinical chronic kidney disease. (14th October 2021) - Stephan, Y; Lima-Posada, I; Souille, M; Bonnard, B; Palacios, R; Nicol, L; Kolkhof, P; Jaisser, F; Mulder, P
Abstract: Background: The steroidal MR antagonist spironolactone and eplerenone reduce mortality in patients with heart failure with reduced ejection fraction (HFrEF) but their use in clinical practice in patients with CKD is limited due to the associated risk of hyperkalemia and worsening renal function. Finerenone is a novel non-steroidal mineralocorticoid receptor antagonist which recently reduced the composite kidney and cardiovascular outcomes in the phase III study FIDELIO among 5734 patients with CKD and type 2 diabetes and a mean baseline eGFR of 44 ml/min/1.73 m 2 . However, the benefit of finerenone on cardiac function in CKD is unknown. Goal: To test the hypothesis that finerenone improves cardiac function in preclinical CKD. Methods: CKD was induced by 5/6 nephrectomy in 10–12 weeks old Sprague Dawley rats and finerenone was administered at the dose of 10 mg/kg/d po as preventive or as curative treatment (starting immediately or 1 month after 5/6 nephrectomy, respectively). LV function / hemodynamics (LV catheterization), LV tissue perfusion (MRI) and GFR (transcutaneous FITC-sinistrin) were assessed in vivo at the age of 24 weeks, as well as LV and kidney weights Results: Twelve weeks after 5/6 nephrectomy, rats showed classical signs of CKD, illustrated by the reduced GFR (1.07±0.09 and 0.46±0.07 ml/min/100g body weight for sham and CKD rats respectively, p<0.05) and increased kidney weight (1.81±0.05 and 2.06±0.22 g respectively; p<0.05) associated with LV diastolic dysfunction, illustrated by the increases in LV end-diastolic pressure (LVEDP; 5.06±0.41 and 9.04±0.88 mmHg respectively, p<0.05), LV relaxation constant (Tau; 9.7±0.3 and 11.2±0.5 msec respectively; p<0.05) and LV end-diastolic pressure volume-relation (LVEDPVR; 1.20±0.11 and 4.43±0.30 mmHg/relative volume unit respectively; p<0.05) without significant changes in LV end-systolic pressure (LVESP; 133±6 and 151±10 mmHg respectively) or LV end-systolic pressure volume-relation (LVESPVR; 27.9±1.3 and 27.9±1.0 mmHg/relative volume unit respectively) while LV perfusion was reduced (9.24±0.22 and 8.01±0.28 ml/min/g LV tissue respectively; p<0.05). Both preventive and curative finerenone treatment did not impact GFR (0.49±0.08 and 0.54±0.09 ml/min/100g body weight) but reduced significantly and to a similar extent, LVEDP (6.68±0.35 and 6.92±0.40 mmHg respectively, p<0.05), Tau (9.0±0.5 and 9.2±0.6 msec, respectively) as well as LV end-diastolic pressure volume-relation (LVEDPVR; 1.97±0.19 and 2.00±0.19 mmHg/relative volume unit respectively; p<0.05) and increased LV tissue perfusion (9.12±0.34 and 9.11±0.71 ml/min/g LV tissue respectively), associated with a normalization of kidney weight (1.86±0.08 and 1.89±0.05 g respectively; p<0.05). Conclusion: Both preventive as well as curative finerenone treatment improves CKD related LV diastolic function, independently from changes in GFR. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Bayer Pharma